Weed density, growth performance and nutrient uptake of basmati rice as affected by weed control measures under direct seeding - Anuradha, S; Vijay, B; Minakshi, S; Raj, K; Vijay, K (Plant Science Today, 2025)
Weed infestation is one of the major constraints limiting the productivity of direct seeded rice (DSR) and there is a need for sustainable and eco-friendly management options beyond sole reliance on herbicides. A field experiment was conducted during the Kharif season of 2022 at the Research Farm, Chatha, Sher-e-Kashmir University of Agricultural Sciences and Technology of Jammu, to evaluate the effect of different weed management practices on growth parameters, weed density and nutrient uptake by weeds under direct seeded basmati rice. The experiment was laid out in a randomized block design with three replications on sandy loam soil. The results revealed that the weed-free treatment was significantly superior in enhancing crop growth parameters, followed by mechanical weeding using a cono-weeder at 20 and 40 days after sowing (DAS). Among the leguminous mulches used as a weed management strategy, surface mulching with dhaincha (Sesbania aculeata) through cutting was the most effective, significantly improving growth parameters over other mulching treatments. Weed density and nutrient uptake by weeds were significantly reduced in treatments involving mechanical weeding twice at 20 and 40 DAS and in surface mulching with cut dhaincha. The study demonstrated that while conventional weed control methods like mechanical weeding and herbicide application remain effective for DSR, alternative eco-friendly approaches such as using leguminous cover crops like dhaincha, especially when cut and used as surface mulch, can also play a substantial role in suppressing weed growth and conserving nutrients for the rice crop. These findings highlight the potential of integrating leguminous mulching strategies into sustainable weed management practices for enhancing DSR productivity.